THE VARIATIONS OF CLINKER SUPERPARAMAGNETIC VALUE FROM PT. SEMEN PADANG BY USING A BARTINGTON MAGNETIC SUSCEPTIBILITY METER SENSOR TYPE B - rina, rina novita; Rifai, Hamdi; Dwiridal, Letmi; Mufit, Fatni (JRFES (Jurnal Riset Fisika Edukasi dan Sains), 2024)
Clinker is a significant material in the cement manufacturing process. Before clinker formation, the raw material is burned in a Rotary Kiln with a temperature of up to 1450℃. After that, it is cooled in a Greet Cooler to a temperature of 100℃ and produces clinker. During the clinker manufacturing process, always being test on samples, but there has been no test based on magnetic susceptibility. The purpose of this research is to know the variation of the superparamagnetic clinker value based on the magnetic susceptibility value. The method used is the rock magnetism method using a Bartington Magnetic Susceptibility Meter MS2B Type. A sampling of clinker is taken hourly every day from PT. Padang Cement. From the value of magnetic susceptibility based on low-field magnetic susceptibility , it was obtained that the values varied from 3.2 × 10-8m3/kg to 22.6 ×10-8m3/kg. The frequency of dependents is also diverse, ranging from 0.0% to 7.4%. Based on the  obtained, the type of grain produced also varies. 136 samples of clinker containing less than 10% superparamagnetic grains, and 32 samples belonging to Medium  have a percentage of 2%-10% where the sample comprises superparamagnetic grains. Between 10% and 75% is a mixture of fine and coarse superparamagnetic grains.